Standardizacija nekaterih kardiocirkulatornih testov pri zdravih otrocih - Meglič, Dušanka (Medicinski razgledi, 1998)
Tests of cardiovascular reflexes and heart rate variability are reliable and noninvasive and therefore useful in children with suspected autonomic nerve dysfunction. The aim of this study was to calculate normal reference values and investigate the relationship between cardiovascular reflex ratios, gender and age. A batery of cardiovascular tests was performed in 81 healthy children, aged 7 to 16 years. The Valsalva, deep breathing, handgrip and orthostatic ratios were calculated and changes in blood pressure were measuredduring handgrip (diastolic) and orthostatic (systolic and diastolic) tests. Heart rate variability was quantified by spectral analysis for low and high frequency bands (LFB and HFB), and the LFB/HFB ratio was calculated. Normal Valsalva, deep breathing, handgrip and orthostatic ratios and integralsof LFB and HFB were calculated for two-year age groups (e.g. 7-8 yearolds, 9-10-years olds etc.) There was a significant negative correlation between the handgrip ratio, systolic blood pressure during orthostatic test, supine LFB/HFB ratio and age. There was also a significant positive correlation between the supine HFB and age. The deep breathing ratio and HFB integral were signifcantly higher in girls aged 11 to 12 years, and the handgrip diastolic pressure increase was greater in girls 15 to 16 yeras of age. Cardiovascular tests are a safe and reliable tool for the evaluation of autonomic nerve function in children. Since age-related variations are more dynamic in children than in adults, we would recommend that reference values for children be determined in groups of smaller age range (e.g. two years). Also, gender grouping should be done when determining reference values in children.
Keywords: heart; Heart function tests; srce; srčna frekvenca; Standards; otroci; Valsalva's maneuver; testiranje; Heart rate; Child; Autonomic nervous system; Pathology; Physiology; Blood pressure